OPTIMASI LAHAN PADA SISTEM TUMPANG SARI JAGUNG MANIS DENGAN KACANG TANAH. KACANG MERAH. DAN BUNCIS PADA SISTEM PERTANIAN ORGANIK - Benny Winson Maryanto Saragih; Nanik Setyowati; Prasetyo Prasetyo; Uswatun Nurjanah (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2019)
The study aimed to determine growth and yield performance of sweet corn, peanut, red bean as well as string bean on either monoculture and intercropping system on organic farming practice and to determine Land Equivalent Ratio (LER) on the intercropping system. The experiment was conducted at CAPS Research Station (1054 m above sea level) from September through December 2018. A single factor evaluated was arranged in Randomized Complete Block Design (RCBD) as follows: monoculture sweet corn, monoculture peanut, monoculture red bean, monoculture string bean, intercropping sweet corn – peanut, intercropping sweet corn – red bean, and intercropping sweet corn – string bean. Each treatment was repeated three times. The results showed, either peanut, red bean, and string bean can’t be intercropped with sweet corn in organic farming practice due to high weed competition. The LER in all intercropping was greater than one indicating than intercropping of intercropping sweet corn – peanut, intercropping sweet corn – red bean and intercropping sweet corn – string bean is more efficient and more productive the monoculture of each crop.